Mental Health and Wellbeing of 9-12-year-old Children in Northern Canada Before the COVID-19 Pandemic and After the First Lockdown - Julia Dabravolskaj; Mohammed K. A. Khan; Paul J. Veugelers; Katerina Maximova; Katerina Maximova (Frontiers Media S.A., 2021)
Objectives: Children's mental health and wellbeing declined during the first COVID-19 lockdown (Spring 2020), particularly among those from disadvantaged settings. We compared mental health and wellbeing of school-aged children observed pre-pandemic in 2018 and after the first lockdown was lifted and schools reopened in Fall 2020.Methods: In 2018, we surveyed 476 grade 4-6 students (9-12 years old) from 11 schools in socioeconomically disadvantaged communities in Northern Canada that participate in a school-based health promotion program targeting healthy lifestyle behaviours and mental wellbeing. In November-December 2020, we surveyed 467 grade 4-6 students in the same schools. The 12 questions in the mental health and wellbeing domain were grouped based on correlation and examined using multivariable logistic regression.Results: There were no notable changes pre-pandemic vs. post-lockdown in responses to each of the 12 questions or any of the sub-groupings.Conclusion: Supporting schools to implement health promotion programs may help mitigate the impact of the pandemic on children's mental health and wellbeing. The findings align with recent calls for schools to remain open as long as possible during the pandemic response.